Association between parental socioeconomic status and offspring overweight/obesity from the China Family Panel Studies: a longitudinal survey. Issue 4 (7th April 2021) - Ding, Suqin; Chen, Jingqi; Dong, Bin; Hu, Jie
Abstract : Objective: To examine the association between parental socioeconomic status (SES) and the risk of offspring overweight/obesity and the changes of the association that occur as children grow older. Design: We used data from the nationally representative longitudinal survey of the China Family Panel Studies of 2010 and its three follow-up waves in 2012, 2014 and 2016. Participants: A total of 6724 children aged 0–15 years old were included. Primary and secondary outcome measures: Average household income and paternal and maternal education levels were used as SES indicators. Logistic regression model for panel data was used to examine the associations between SES indicators and child overweight/obesity. A restricted cubic spline linear regression model was used to estimate body mass index (BMI) trajectories with child growth across parental SES levels. Results: Compared with the lowest education level (primary school or less), the ORs for fathers who had completed junior high school, senior high school and junior college or higher were 0.85 (95% CI 0.75 to 0.97), 0.77 (95% CI 0.64 to 0.92) and 0.72 (95% CI 0.55 to 0.93), respectively. The corresponding ORs for mothers were 0.76 (95% CI 0.67 to 0.86), 0.59 (95% CI 0.47 to 0.72) and 0.45 (95% CI 0.34 to 0.60), respectively. A negative association between parental education and offspring overweight/obesity was observed in the first 10 years but not in children 11–15 years old. BMI differences across parental education levels emerged from birth and widened before 6–7 years old, but decreased before adolescence. High average household income was related to a low risk of offspring overweight/obesity but not when parental education level was adjusted for. Conclusion: High parental education levels were associated with a low risk of offspring overweight/obesity, especially before adolescence. Effective approaches need to be adopted in early childhood to reduce socioeconomic differences in overweight/obesity.